The Effect Of Time Driven Activity Based Costing in Pricing Decisions (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The research aims to demonstrate the impact of TDABC as a strategic technology compatible with the rapid developments and changes in the contemporary business environment) on pricing decisions. As TDABC provides a new philosophy in the process of allocating indirect costs through time directives of resources and activities to the goal of cost, identifying unused energy and associated costs, which provides the management of economic units with financial and non-financial information that helps them in the complex and dangerous decision-making process. Of pricing decisions. To achieve better pricing decisions in light of the endeavor to maintain customers in a highly competitive environment and a variety of alternatives, the research chooses a random sample represented by the Kufa cement plant in Najaf, including an intentional sample represented by advanced, intermediate and operational administrative cadres as well as accounting cadres of (67) individuals to reach results This effect, and then analyzing the data using the statistical program (SPSS) for the purpose of testing research hypotheses, and a set of other statistical measures.The research reached a set of results, the most important of which is that TDABC has a positive effect in supporting pricing decisions through its contribution to providing financial and non-financial information through which it can achieve a reduction in costs. As for the recommendations presented by the current research, it is understood that TDABC should be applied in the research sample due to its accuracy in allocating indirect costs, identifying and measuring unused energy costs, and contributing to providing support for pricing decisions.